2017
DOI: 10.3892/etm.2017.5000
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2 and dectin-1 function as promising biomarker for Aspergillus fumigatus infection

Abstract: Abstract. In recent years, along with the wide application of organ transplantation and immunosuppressive agents, as well as the abuse of broad spectrum antibiotics, the incidence of invasive fungal infections has been increasing gradually. The present study aimed to identify novel biomarkers in cells infected with Aspergillus fumigatus. Human umbilical vein endothelial cells (HUVECs) were infected with Asper gillus fumigatus and then harvested at different time-points (0, 1, 2, 4 and 6 h). The expression Toll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The results showed that PAMPs recognized by TLR2 upregulated IL-10 and decreased the recruitment of pulmonary eosinophils, thus downregulating Th2 response. 370 , 371 In allergic asthma, TLR9–IL-2 affects the Th2 response by regulating the expression of IL-17A, so small molecule inhibitors targeting TLR9 may become a new treatment strategy. 372 …”
Section: Prr-related Diseasesmentioning
confidence: 99%
“…The results showed that PAMPs recognized by TLR2 upregulated IL-10 and decreased the recruitment of pulmonary eosinophils, thus downregulating Th2 response. 370 , 371 In allergic asthma, TLR9–IL-2 affects the Th2 response by regulating the expression of IL-17A, so small molecule inhibitors targeting TLR9 may become a new treatment strategy. 372 …”
Section: Prr-related Diseasesmentioning
confidence: 99%
“…In a study of human umbilical vein endothelial cells infected with Aspergillus fumigatus , it was found that dectin-1 was able to bind to the surface of A. fumigatus and dispersed inside and outside the cell. The expression of dectin-1 in cells infected with Aspergillus fumigation was significantly higher than that in the control group ( Zhang et al., 2017 ). Previous in vivo studies have shown that mice without dectin-1 expression have significantly increased fungal load in lung tissue after nasal injection of Aspergillus fumigatus compared with wild-type mice ( Werner et al., 2009 ).…”
Section: Discussionmentioning
confidence: 93%